Cosmology yesterday and today - witnessing a piece of history - Heller, Michał (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2010)
Short recollections of an author who with his own eyes witnessed the development of cosmology from purely theoretical speculations to the mature experimental science.